Middle managers, their organization and knowledge sharing: Examination of knowledge sharing maturity (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The purpose of this paper is to highlight the role of middle managers in the knowledge sharing process by presenting the results of a survey aiming to reveal the elements of middle managers knowledge sharing maturity and individual and organizational characteristics affecting them. The paper is based on quantitative research. The data were gathered through questionnaires. Based on 400 usable survey responses, the authors applied principal component analysis, decision tree, analysis of variance, and post-hoc test to reveal the elements of middle managers knowledge sharing maturity and the differences individual and organizational characteristics result in them. The study results indicate that middle managers knowledge sharing maturity is measured with four elements and based on individual and organizational characteristics there are differences in certain elements. The originality of the paper is that past research did not investigate middle managers or their knowledge sharing maturity, only focused on the organizational level of knowledge management maturity. The effect of individual and organizational characteristics on knowledge sharing maturity has not been investigated either. This paper focuses on these aspects. The results of the survey could help not only middle managers, but top managers and other employees as well in learning how to foster knowledge sharing.